Multi criteria optimization of plate heat exchanger for super critical CO2 power systems. (September 2017) - Lillo, Gianluca; Mastrullo, Rita; Mauro, Alfonso W.; Viscito, Luca
Abstract: Supercritical CO2 power systems are an interesting option to allow the use of low grade thermal sources, especially for small size plants, where compactness and costs are of primary importance in order to spread their use; in such applications innovative plate heat exchangers, able to work at high pressure, could be used. In this paper a model for detailed heat transfer and pressure drop calculations is presented and used to carry-out an analysis oriented to the definition of a map, presented according to the criteria of size of the heat exchanged and total performance index, in order to look for the best trade-off between component cost and energetic performance.